2016
DOI: 10.5430/jst.v6n2p56
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a teaching program on outcome quality of white light transurethral resection for bladder tumor: A cohort study

Abstract: Objective: To test the hypothesis that a teaching program improves the quality of transurethral resection of bladder tumor (TURBT) and decreases the risk of early recurrence. Material and methods: This is an observational retrospective cohort study of prospectively recorded data of patients with first clinical diagnosis of non-muscle-invasive bladder cancer (NMIBC), scheduled for TURBT. In 2005 a systematic TURBT teaching program was introduced in our Department. We reviewed the charts of patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The effect of training and resultant surgical experience on the presence of detrusor muscle was evident in a study from tertiary center, in which multivariable logistic analysis showed that the establishment of a training program was an independent prognostic factor for the rate of presence of DM (OR = 3.92, 95% CI = 2.42-6.33). 9 However, the between-surgeon differences in the recurrence risk were not that pronounced for smaller tumors. Mariappan et al 10 showed that the presence of detrusor muscle in the first specimen and surgeon's experience were the two factors that were significantly associated with a lower recurrence rate.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The effect of training and resultant surgical experience on the presence of detrusor muscle was evident in a study from tertiary center, in which multivariable logistic analysis showed that the establishment of a training program was an independent prognostic factor for the rate of presence of DM (OR = 3.92, 95% CI = 2.42-6.33). 9 However, the between-surgeon differences in the recurrence risk were not that pronounced for smaller tumors. Mariappan et al 10 showed that the presence of detrusor muscle in the first specimen and surgeon's experience were the two factors that were significantly associated with a lower recurrence rate.…”
Section: Discussionmentioning
confidence: 94%
“…The effect of training and resultant surgical experience on the presence of detrusor muscle was evident in a study from tertiary center, in which multivariable logistic analysis showed that the establishment of a training program was an independent prognostic factor for the rate of presence of DM (OR = 3.92, 95% CI = 2.42–6.33). 9…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedure was performed according 122 to the standard technique at our institution which are 123 in line with the EAU guidelines and take into account 124 the TURBT pre-operative checklist [16,17].…”
Section: Methodsmentioning
confidence: 99%